Identification of Novel Virulence-Associated Proteins Secreted to Xylem by Verticillium nonalfalfae During Colonization of Hop Plants - Marko Flajsman; Stanislav Mandelc; Sebastjan Radisek; Natasa Stajner; Jernej Jakse; Katarina Kosmelj; Branka Javornik (Molecular Plant-Microbe Interactions, 2016)
Plant pathogens employ various secreted proteins to suppress host immunity for their successful host colonization. Identification and characterization of pathogen-secreted proteins can contribute to an understanding of the pathogenicity mechanism and help in disease control. We used proteomics to search for proteins secreted to xylem by the vascular pathogen Verticillium nonalfalfae during colonization of hop plants. Three highly abundant fungal proteins were identified: two enzymes, α-N-arabinofuranosidase (VnaAbf4.216) and peroxidase (VnaPRX1.1277), and one small secreted hypothetical protein (VnaSSP4.2). These are the first secreted proteins so far identified in xylem sap following infection with Verticillium spp. VnaPRX1.1277, classified as a heme-containing peroxidase from Class II, similar to other Verticillium spp. lignin-degrading peroxidases, and VnaSSP4.2, a 14-kDa cysteine-containing protein with unknown function and with a close homolog in related V. alfalfae strains, were further examined. The in planta expression of VnaPRX1.1277 and VnaSSP4.2 genes increased with the progression of colonization, implicating their role in fungal virulence. Indeed, V. nonalfalfae deletion mutants of both genes exhibited attenuated virulence on hop plants, which returned to the level of the wild-type pathogenicity in the knockout complementation lines, supporting VnaPRX1.1277 and VnaSSP4.2 as virulence factors required to promote V. nonalfalfae colonization of hop plants.